Implementasi social emotional learning dalam muatan pembelajaran matematika materi pengukuran kelas IV sekolah dasar - Tri Cahyaning Tyas; Retno Winarni; Anesa Surya (Jurnal Pendidikan Dasar, 2025)
The purpose of this study is to determine the implementation of social emotional learning in the content of mathematics learning measurement material in elementary schools. The research approach used is a qualitative approach with a case study research method. Data collection techniques using triangulation with interviews, observation, and documentation studies. The data analysis technique uses Creswell's opinion with six stages of analysis. The results of the research that has been done show that social emotional learning can improve students' mathematics learning outcomes indirectly so it is important that this social emotional learning is applied.